2020
DOI: 10.3390/ijms21217827
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NPB, NPW and Their Receptor in the Rat Heart

Abstract: Members of neuropeptide B/W signaling system have been predominantly detected and mapped within the CNS. In the rat, this system includes neuropeptide B (NPB), neuropeptide W (NPW) and their specific receptor NPBWR1. This signaling system has a wide spectrum of functions including a role in modulation of inflammatory pain and neuroendocrine functions. Expression of NPB, NPW and NPBWR1 in separate heart compartments, dorsal root ganglia (DRG) and stellate ganglia was proven by RT-qPCR, Western blot (WB) and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Neuropeptide B is widely expressed in the organism, predominantly in the central nervous system [ 106 , 120 , 121 ], as well as in peripheral tissues, such as the gastrointestinal system, heart, ovary, testes, adrenals, pancreatic islets, and fat tissue [ 118 , 121 , 122 , 123 ]. Neuropeptide B was implicated in controlling appetite [ 108 ], inflammatory pain [ 124 ], stress hormone secretion [ 125 ], and the stimulation of aldosterone [ 126 ], insulin [ 118 ], progesterone, and testosterone [ 127 ].…”
Section: Neuropeptide B and Neuropeptide Wmentioning
confidence: 99%
“…Neuropeptide B is widely expressed in the organism, predominantly in the central nervous system [ 106 , 120 , 121 ], as well as in peripheral tissues, such as the gastrointestinal system, heart, ovary, testes, adrenals, pancreatic islets, and fat tissue [ 118 , 121 , 122 , 123 ]. Neuropeptide B was implicated in controlling appetite [ 108 ], inflammatory pain [ 124 ], stress hormone secretion [ 125 ], and the stimulation of aldosterone [ 126 ], insulin [ 118 ], progesterone, and testosterone [ 127 ].…”
Section: Neuropeptide B and Neuropeptide Wmentioning
confidence: 99%
“…These results indicate that NPB may contribute to the modulation of bone cell activity. In addition, discussing the role of NPB in peripheral tissues, it needs to be pointed out that a recent rat study demonstrated that NPB and its receptors are present in the heart [ 25 ]. NPB mRNA expression was detected in both atria and, at lower levels, both ventricles.…”
Section: Other Effects Of Npbmentioning
confidence: 99%
“…Due to limited data regarding the role of NPB in the cardiovascular system, it is difficult to speculate about its role in the heart. Nevertheless, based on the presence of NPB in smooth muscle cells of the coronary circulation, it was postulated that it may be involved in modulating the regulation of the coronary circulation [ 25 ]. Moreover, NPB expression was also detected in the intestine [ 10 , 18 , 21 , 23 ], suggesting its potential role in controlling the gut–brain axis.…”
Section: Other Effects Of Npbmentioning
confidence: 99%
“…After drying, the slide was placed on an inverted microscope. This staining was used because it does not interfere with RNA as well as protein analyses [17,18].…”
Section: Preparation Of Lcm Sectionmentioning
confidence: 99%